Relationship Between Nutrition Knowledge and Body Mass Index (BMI) in Nutrition Students - Herviana, Herviana; Anggraini, Citra Dewi; Rosyidah, Haqqelni Nur; Desy; Rizma, Amalina (Future Science, 2024)
The balance of nutritional consumption with metabolic needs in the body has an impact on an individual's nutritional status. Knowledge is included in one of the factors that influence an individual's nutritional status. This research aims to ensure the level of nutrition knowledge had a relation to the Body Mass Index (BMI) of students in Kepulauan Riau. The approach used in this research used a cross-sectional research design. The sample used in this research was 50 students of the undergraduate program of nutrition science in Kepulauan Riau. Nutritional knowledge data was collected by using an electronic questionnaire and BMI was measured by weight and height. Data was analyzed by descriptive and regression. The results showed that the average nutrition knowledge score was in the medium category (66.6±12.34). Whereas BMI score shows that 62% of students have got normal BMI, while 20% and 18% are overweight and underweight. Regression analyses showed that r=0.172 with p=0.233. Our findings stated that nutritional knowledge had no significant difference in BMI.